Policy Makers’ Perceptions on Implementation of National Action Plans on Antimicrobial Resistance in South Africa and Eswatini Using Coordination, Accountability, Resourcing, Regulation and Ownership Framework (2018–2019) - Kholiwe Shabangu; Sabiha Yusuf Essack; Sinegugu Evidence Duma (Antibiotics)
Background: Antimicrobial resistance (AMR) is a global threat that affects humans, animals, plants, the environment, societies, and economies—requiring urgent coordinated action. In May 2015, the World Health Assembly (WHA) adopted the Global Action Plan (GAP) on AMR, urging member states to develop and implement their own National Action Plans (NAPs) using a One Health approach. Objective: Both South Africa and Eswatini have developed NAPs and are currently in the implementation phase. However, no study has explored policymakers’ perceptions regarding NAP implementation particularly concerning coordination, accountability, resourcing, regulation and ownership. Methods: This qualitative study employed a narrative approach to explore these perceptions in South Africa and Eswatini. A total of 36 key informants were recruited using purposive and snowball sampling methods. Data was collected between November 2018 and March 2019 and transcribed verbatim. Results: Findings revealed that while governance structures for implementing NAPs exist in South Africa and Eswatini, several critical areas require urgent attention. These include limited accountability across One Health sectors, the absence of dedicated national budgets for NAP implementation, poor intra- and inter- ministerial coordination, weak medicine regulation and enforcement, and delayed multisectoral ownership of the NAPs. Conclusions: To address AMR effectively, both countries must allocate dedicated budgets, improve multisectoral integration, and strengthen regulatory frameworks regarding antimicrobial access and use across all One Health sectors. A firm commitment from all sectors is required—not just formal endorsement of the NAPs—to ensure sustainable implementation and ownership.